PENGARUH PELATIHAN, DISIPLIN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLAAN KEUANGAN DAN ASSET DAERAH PROVINSI SULAWESI TENGAH - Munir, Andi Abdul (Katalogis, 2017)
The study is aimed to: 1) determine and analyze simultaneous influence of training, discipline, and motivation on the performance of officials in The Agency of Financial and Local Asset Administrator in Central Sulawesi; 2) determine and analyze the influence of training on the performance of officials in The Agency of Financial and Local Asset Administrator in Central Sulawesi; 3) determine and analyze the influence of discipline on the performance of officials in The Agency of Financial and Local Asset Administrator in Central Sulawesi; 4) determine and analyze the influence of motivation on the performance of officials in The Agency of Financial And Local Asset Administrator in Central Sulawesi. Sample consists of 79 officials who were selected through disproportionate stratified random sampling by which sample is randomly selected proportionally. Technique of analysis uses multiple linear regressions has shown that training, discipline, and motivation simultaneously have significant influence on the performance of officials in The Agency of Financial and Local Asset Administrator in Central Sulawesi with Sig F of 0.000 < α 0.05. Training has positive and significant influence on official’s performance with sig-t (X1) of 0.000 < α 0.05; discipline has positive and significant influence on the performance of officials in The Agency of Financial and Local Asset Administrator in Central Sulawesi with Sig-t (X2) of 0.035 < α 0.05; and motivation has positive and significant influence on the performance of officials with sig-t (X3) of 0.017 < α 0.05.